MODUL PERMAINAN OUTBOUND UNTUK MENINGKATKAN KEPERCAYAAN DIRI SISWA KELAS VII SMP NEGERI 1 PEKANBARU - Siti Hajar; Zulfan Saam; Rosmawati Rosmawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study aims to develop an outbound game module in order to increase the confidence of grade VII students of SMP Negeri 1 Pekanbaru. The type of research used is research and development or Research and Development (R&D). Through 6 step, namely (1) potential and problems, (2) data collection, (3) product design, (4) design validation, (5) design revision, (6) product creation. To make the module more perfect, this study conducted a validation test with 2 material experts and 2 practitioners. Data collection techniques in this study used literature studies and validation questionnaires. The data analysis technique used qualitative and quantitative analysis. The results of the module feasibility test as a whole from the aspects of content feasibility, language feasibility and graphic feasibility get an assessment of 67.91%, it shows that the outbound game module to increase the confidence of grade VII students of SMP Negeri 1 Pekanbaru can be said to be feasible to be tested as an ingredient in provision of BK services in schools.Key Words: R&D, Outbound Game Module, Self-Confidence